Organometallic catalysis: some contributions to organic synthesis - Elena V. Gusevskaya (Química Nova, 2003)
In the present paper some general aspects of metal complex catalysis and its applications for oxyfunctionalization of various olefins, including naturally occurring ones, via selective oxidation, hydroformylation and alkoxycarbonylation are discussed.